Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan pada Kantor Direksi PT. Perkebunan Nusantara XIV - Firdaus, Muh; Sari, Ratna Candra; Ansyari, Muhammad Ilyas Nur (Jurnal Ecogen, 2024)
This research objektives to determine the influence of leadership style and work discipline on employee performance at the Office of the Directors of PT. Perkebunan Nusantara XIV. This research uses quantitative methodology. The population in this study reached 140 people; using the Slovin technique formula, several up to 58 respondents were found. Data was collected through a research questionnaire using SPSS 26 statistical analysis. The research results show that leadership style significantly affects employee performance, and work discipline partially substantially impacts employee performance. Then, leadership style and work discipline were tested simultaneously, which greatly influenced employee performance. This research contributes to the influence of leadership style and work discipline on employee performance, which is still very limited. Apart from that, the research results can be used by companies to determine policies related to improving employee performance.